Kemampuan Prospektif Fusan FP4 dalam Memproduksi Inulinase dan Profil Pertumbuhannya - Wijanarka Wijanarka; Ika Anggraini (Jurnal Biologi Papua, 2017)
Fusan FP4 is one type fused materials derived from intraspecific fusion of Pichia manshurca. The fused materials have superior capabilities compared with other materials, especially in producing inulinase enzyme (E.C. 3.2.1.7). The aims of the study are to determine the production of the enzyme inulinase of fusan FP4 and the growth profile formed. Growth can be detected by the addition of size and cell division. Growth measurements of fusan FP4 was carried out for 24 hours and observation and sampling was done every 6 hours for 24 hours. Observations of growth are conducted qualitatively by using a spectrophotometer, while the production of inulinase done using DNS method. The results of this study showed that the highest inulinase production was 1.948 U/ml and occurred at log phase with 6 hours of incubation time (t6) to 12 hours (t12). Key words: inulinase, Fusan FP4, log phase, P. manshurca.